Predictors of adverse postoperative course of cholecystectomy in mini-incision access and laparoscopic cholecystectomy - V. N. Klimenko; D. V. Syvolap; S. M. Kravchenko; V. V. Vakulenko; A. V. Zakharchuk (Zaporožskij Medicinskij Žurnal)
Background. Shift from laparotomy to laparoscopy qualitatively changed surgery aggressiveness, allowed to reduce the number and severity of postoperative complications. New methods of minimally invasive interventions introduction have generated a number of legitimate questions relating to the desirability, safety, possible range of applications, the effectiveness of interventions. However, no studies in the literature devoted to the development of criteria for predicting the likely complications of surgical data and adverse postoperative course.